Do economic shocks have a sustained effect on the height of 5-year-old children? Evidence from rural and urban Ethiopia - Woldehanna, T (Palgrave Macmillan, 2012)
Reductions in child mortality and illness are often considered the main indicators of social development. As a result, one of the targets of the Millennium Development Goals is reducing child and infant mortality rates by two-thirds. In the Ethiopian context, the target set by the national survival strategy is to reduce the under-five mortality rate from 140 to 85 per 1,000 births and the infant mortality rate from 97 to 45 per 1,000 births by 2015 (MoFED 2006a, 2006b: 117). The nutrition of children is key to reducing these mortality rates since malnutrition is currently the leading cause of disease globally (Ezzati et al. 2002) and has been identified as the underlying factor in about 50 per cent of deaths of children under five years of age in developing countries (Frimpong and Pongou 2006: 3; Black et al. 2003). Ethiopia’s Health Sector Development Program (FMoH, 2005: 39) lists malnutrition as one of the major causes of child mortality, together with pneumonia, neonatal conditions, malaria, diarrhoea, measles, and HIV/AIDS.